Why have Indonesian murderers not paid victims' heirs? - Nurcahyo, Nanang; Manitra, Ramalina Ranaivo Mikea (Journal of Law, Environmental and Justice, 2023)
The crime of murder results in material and non-material losses for the victims who experience it. The families of victims murder crimes or the heirs are the ones who suffer the most losses following a murder incident that claims the lives of family members or loved ones. Criminal law in Indonesia still does not really prioritize punishment in the form of compensation, so that if heirs want to get compensation they have to submit an application or go through a separate route, this results in the value of substantial justice in criminal law not being upheld, this is proven by the lack of obligations. Compensation in the form of restitution that is mandatory for perpetrators of crimes. To respond it, a new way of upholding substantial justice is needed. By using doctrinal research methods, pre-existing legal sources related to the research theme are searched for. The research results show that several efforts are needed to uphold substantial justice in criminal law, namely the re-actualization of criminal law and the provision of a special forum for heirs to demand compensation directly. In this way, substantial justice can be upheld in criminal law and without going through requests or independent efforts